Carbazole modified iridium complex, electro-polymerization film based on iridium complex, and preparation method and application of electro-polymerization film
By modifying the iridium (III) complex and preparing an electrically polymerized film, the problems of insufficient stability of porous materials in harsh environments and immature functional maturity of metal-free COFs are solved, and efficient performance in energy conversion and oxygen sensing are achieved.
Patent Information
- Application Number
- CN202510065051.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-29
AI Technical Summary
The existing porous materials are insufficient in harsh chemical environments, and the metal-free COFs are not functionally mature, making it difficult to meet the needs of modern science.
A carbazole modified iridium (III) complex was prepared and modified onto the ITO electrode by a constant potential polymerization method to prepare an electrical polymerized film with potential energy conversion and oxygen sensing applications.
The film exhibits high photocurrent density and efficiency in energy conversion and oxygen sensing, and has potential application prospects.
Smart Images

Figure CN119899215A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photoelectric sensors, and in particular to a carbazole-modified iridium complex and an electropolymerized film based on the iridium complex, and a preparation method and application thereof. Background Art
[0002] Over the past two decades, porous materials (APMs) - including metal-organic frameworks (MOFs), covalent organic frameworks (COFs), porous organic polymers (POPs) supramolecular frameworks, zeolites and other materials have been developed and explored in many fields. In particular, MOFs and COFs have attracted much attention from scientists for their ability to extend the precision of molecular chemistry to the framework. MOFs are composed of metal-oxide units connected by organic linkers with metal-coordination bonds. Although MOFs provide a wide range of combinations of metal ions and organic linkers to achieve the desired structure and function, the relative strength of the coordination bonds often limits their practical application, especially under very harsh conditions. To address these shortcomings, COFs have been proposed as a completely organic alternative architecture to MOFs. While COFs have many advantages of high crystallinity, porosity and tunability of MOF materials, their structures can also show high stability in harsh chemical environments such as boiling water, strong acids and bases, and redox reactions. This advantage has attracted a lot of research interest, hoping to not only complement but also surpass the development of other known crystalline porous materials such as MOFs and zeolites. In general, COFs are composed entirely of light elements, which imposes some intrinsic limitations on their physical and chemical properties. For example, the relatively low density and weak interlayer molecular forces lead to high hydrophobicity resulting from loose packing when preparing two-dimensional COF membranes or films, which is not compatible with the surface compatibility of materials chemistry and the biocompatibility of biological systems. More critically, metal-free COFs usually exhibit immature functions and cannot meet the requirements of modern science. In contrast, recent developments in solid porous materials in the fields of gas adsorption and separation, heterogeneous catalysis, and electrochemical energy storage have emphasized the role of metals in their structures. Targeted introduction of metal ions into porous COFs to form metal covalent organic frameworks (MCOFs) may help address these shortcomings. In a sense, MCOFs can build a bridge between MOFs and COFs, with the latter exhibiting a balanced combination of crystallinity, porosity, stability, and tunability, leading to self-complementary features between the two materials. It is an indisputable fact that MCOFs have become an interdisciplinary subject between polymer chemistry and inorganic chemistry. However, the development of MCOFs is still in its infancy and will still face challenges in the next few years. The present invention prepares a carbazole-modified iridium (III) complex that has not been reported in the literature and an electropolymerized film based on the iridium (III) complex. Summary of the invention
[0003] The purpose of the present invention is to provide a carbazole-modified iridium complex and an electropolymerized film based on the iridium complex, and a preparation method and application thereof in view of the above-mentioned problems. The present invention polymerizes the complex onto ITO conductive glass by a constant potential polymerization method to prepare an electropolymerized film based on the iridium (III) complex, and the film has potential application prospects in energy conversion and oxygen sensing.
[0004] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0005] Provided is a carbazole-modified iridium complex, the structural formula of which is shown in formula (I):
[0006]
[0007] The chemical formula is [Ir(ppy) 2 HL]PF 6 , wherein ppy represents 2-phenylpyridine, and HL is a ligand. The ligand HL is N-(4-(9H-carbazole-9-yl)phenyl)-4-(9H-carbazole-9-yl)-N-(4-(3a,11b-dihydro-1H-imidazo[4,5-f][1,10]phenanthroline-2-yl)phenyl)aniline, and the structural formula is shown in formula (II):
[0008]
[0009] A method for preparing a carbazole-modified iridium complex is provided, comprising the following steps:
[0010] (1) Synthesis of ligand HL: 4-(bis(4-(9H-carbazole-9-yl)phenyl)amino)benzaldehyde, ammonium acetate, and 1,10-phenanthroline-5,6-dione were placed in a reaction vessel, glacial acetic acid was added, and the reaction was carried out at 120±1°C. After the reaction was completed, the reaction solution was quickly poured into ice water, the pH of the mixed solution was adjusted to neutral, and the solution was allowed to stand for a while. After the precipitate was separated, it was filtered by suction, and the filter cake was washed with distilled water. The crude product was washed with DMF / H2O. 2 O mixed solvent recrystallization, filtration, collection of precipitates, washing the filter cake with anhydrous ethanol, vacuum drying, the obtained powder is the ligand HL;
[0011] (2) Complex [Ir(ppy) 2 HL]PF 6 Synthesis: [Ir(ppy) 2 (μ-Cl)] 2 , ligand HL in a flask, and add ethylene glycol monoethyl ether, reflux reaction under light-proof and nitrogen protection; after the reaction is completed and cooled to room temperature, add NH 4 PF 6, spin-dried to obtain a crude product; the crude product was dissolved in dichloromethane, separated and purified by thin layer chromatography on a silica gel column, the orange band was collected, and most of the solvent was removed by rotary evaporation. Hexane was added until the precipitate was completely precipitated, filtered, the filter cake was washed with hexane, and vacuum dried to obtain a yellow powder.
[0012] In the present invention, preferably, in step (1), the molar ratio of 4-(bis(4-(9H-carbazole-9-yl)phenyl)amino)benzaldehyde to 1,10-phenanthroline-5,6-dione is 1:1.
[0013] In the present invention, preferably, in step (2), the [Ir(ppy) 2 (μ-Cl)] 2、 Ligands HL and NH 4 PF 6 The molar ratio is 1:2:10-20.
[0014] In the present invention, preferably, in step (2), the eluent used for separation and purification is dichloromethane / methanol in a volume ratio of 30:1.
[0015] The invention provides an electropolymerized film based on an iridium complex, which is an electropolymerized film obtained by modifying the iridium complex onto an ITO electrode using a constant potential electropolymerization method. Specifically, the method comprises the following steps: first, the ITO glass electrode is cleaned, and then, the complex [Ir(ppy) 2 HL]PF 6 It was dissolved in a dichloromethane solution containing tetrabutylammonium hexafluorophosphate as a supporting electrolyte, with an ITO substrate as the working electrode and a platinum electrode as the counter electrode. 3 The electrode is used as a reference electrode, and under nitrogen protection, constant potential method is used for electropolymerization to prepare Ir(III) complex 3D film. In this preparation method, the iridium complex [Ir(ppy) 2 HL]PF 6 The concentration in dichloromethane is 1 mM.
[0016] The application of the electropolymer film provided refers to the application of the electropolymer film in energy conversion and oxygen sensor.
[0017] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0018] The present invention prepares a carbazole-modified metal iridium (III) complex and modifies it onto an ITO electrode by constant potential electropolymerization. The photoelectric property study results show that when the constant potential polymerization time is 60s and the applied bias voltage is -0.4V, the photocurrent of the obtained film is the largest, at 100mW / cm 2 Under white light, 0.1M Na2 SO 4 The maximum photocurrent density of the iridium (III) complex film in aqueous solution after constant potential electropolymerization for 60s can reach 7.00μA / cm 2 When oxygen is introduced into the electrolyte solution, the photocurrent density increases to 14.03 μA / cm 2 . This shows that the film has potential application prospects in energy conversion and oxygen sensing. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The i-t curves of the Ir(III) complex 3D film at a bias voltage of -0.4 V for constant potential polymerization of different times (20s, 40s, 60s, 80s, 100s);
[0020] Figure 2 During constant potential electropolymerization for 60 s, the it curves of the Ir(III) complex 3D film at bias voltages of -0.4 V, -0.3 V, -0.2 V, -0.1 V, 0 V, +0.1 V, +0.2 V, +0.3 V, and +0.4 V;
[0021] Figure 3 The photocurrent response of the Ir(III) complex 3D film in an electrolyte balanced with nitrogen, air, and oxygen at a bias voltage of -0.4 V for 60 s of constant potential electropolymerization.
[0022] Figure 4 Comparison of the photoelectric conversion efficiency of the Ir(III) complex film and the visible absorption spectrum of the film during constant potential electropolymerization for 60s. DETAILED DESCRIPTION
[0023] The technical scheme of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. In the embodiments of the present invention, the raw material 4-(bis(4-(9H-carbazole-9-yl)phenyl)amino)benzaldehyde is synthesized by the method in the reference (Self-host homoleptic green iridium dendrimers based on diphenylaminedendrons for highly efficient single-layer PhOLEDs, Wenwen Tian etc. Journal of Materials Chemistry C, Published on 11 November 2013), and other raw materials are purchased from commercial channels.
[0024] Example 1 Preparation of ligand HL
[0025] The synthetic route of the ligand N-(4-(9H-carbazole-9-yl)phenyl)-4-(9H-carbazole-9-yl)-N-(4-(3a,11b-dihydro-1H-imidazo[4,5-f][1,10]phenanthroline-2-yl)phenyl)aniline (HL) is as follows:
[0026]
[0027] The synthesis method is as follows: 4-(bis(4-(9H-carbazole-9-yl)phenyl)amino)benzaldehyde (603 mg, 1.0 mmol), ammonium acetate (1.54 g, 20 mmol), and 1,10-phenanthroline-5,6-dione (210 mg, 1.0 mmol) are placed in a flask, glacial acetic acid (20 mL) is added, and the mixture is reacted at 120±1°C for 2 h. After the reaction is completed, the reaction solution is quickly poured into 200 mL of ice water, and the pH of the mixed solution is adjusted to neutral with ammonia water. The mixture is allowed to stand for a while, and the precipitate is filtered after being separated. The filter cake is washed with distilled water, and the crude product is purified by filtration with DMF / H 2 O (V / V=4 / 1) was recrystallized and filtered to collect the precipitate. The filter cake was washed with anhydrous ethanol and dried in vacuo to obtain 0.48 g of a yellow-brown powder with a yield of 60%.
[0028] 1 H-NMR (δ / ppm, 500 MHz, DMSO-d 6): 8.27 (d, J = 5Hz, 5H), 7.88 (d, J = 7.5Hz, 2H), 7.72 (d, J = 7.0Hz, 3H), 7.58 (d, J = 8.0Hz, 3H), 7.51-7.46 (m, 14H), 7.33-7.30 (m, 7H).
[0029] Example 2 Complex [Ir(ppy) 2 HL]PF 6 Preparation
[0030] Complex [Ir(ppy) 2 HL]PF 6 The synthetic route is as follows:
[0031]
[0032] The synthesis method is: [Ir(ppy) 2 (μ-Cl)] 2 (100 mg, 0.10 mmol), ligand HL (160 mg, 0.20 mmol) were placed in a flask, 20 mL of ethylene glycol monoethyl ether was added, and the mixture was refluxed for 12 h under the protection of nitrogen and light protection. After the reaction was completed and cooled to room temperature, NH 4 PF 6 (0.32 g, 2.0 mmol), spin-dried to obtain a crude product. The crude product was dissolved in dichloromethane, separated and purified by thin layer chromatography on a silica gel column, the eluent was dichloromethane / methanol (V:V=30:1), the orange band was collected, and most of the solvent was removed by rotary evaporation, and n-hexane was added until the precipitate was completely precipitated, filtered, the filter cake was washed with n-hexane, and vacuum dried to obtain 0.0923 g of yellow powder, with a yield of 36.7%.
[0033] 1 H-NMR (δ / ppm, 500MHz, DMSO-d 6 ): 8.41 (d, J=8Hz, 2H), 8.28 (d, J=7.5Hz, 6H), 8.15 (s, 2H), 8.08 (t, J=7.5Hz, 2H), 7.96 (d, J=7.5Hz, 2H), 7.89 (t, J=7.5Hz, 2H), 7.70 ( t, 8.5Hz, 4H), 7.55-7.46 (m, 18H), 7.32 (t, J=6.5Hz, 4H), 7.07 (t, J=7.0Hz, 2H), 6.99 (dt, J=22Hz, 6.5Hz, 4H), 6.31 (d, J=7.5Hz, 2H).
[0034] Mass spectrometry (MALDI-TOF MS) calculated value: 1294.39 [M-PF6 - ] + ; Experimental value: 1295.101[M-PF 6 - ] + .
[0035] Elemental analysis (%): C 77 H 51 Ir 9 PF 6 1.5H 2 O Calculated: C 63.06, H 3.71, N 8.60; Found: C 63.03, H 3.68, N 8.52.
[0036] It can be seen that the structure of the prepared target complex is correct.
[0037] Example 3 Preparation method of Ir(III) complex 3D film
[0038] The preparation route of carbazole-modified Ir(III) complex 3D thin film is as follows:
[0039]
[0040] The synthesis method is:
[0041] (1) Cleaning of ITO glass electrode: The ITO substrate was ultrasonically treated with detergent water for 20 min to remove surface stains, and then cleaned with distilled water for 3 times, each time for 5 min. 3 ·H 2 O:H 2 O 2 :H 2 O (V:V:V=1:1:5) mixed solution, boiled at 70℃ for 40min, cleaned with distilled water ultrasonically, and then washed with N 2 Blow dry and set aside.
[0042] (2) Preparation of carbazole-modified iridium complex thin film electrode: The complex [Ir(ppy) 2 HL]PF 6 Dissolved in a dichloromethane solution containing 0.05M tetrabutylammonium hexafluorophosphate as a supporting electrolyte, the complex [Ir(ppy) 2 HL]PF 6 The concentration of Ag / AgNO was 1mM, the ITO substrate was used as the working electrode, the platinum electrode was used as the counter electrode, and the 3 The electrode was used as a reference electrode, and under nitrogen protection, constant potential electropolymerization was performed with a time gradient of 20 s to prepare Ir(III) complex 3D films of different thicknesses.
[0043] Example 4 Photoelectrochemical properties of Ir(III) complex 3D thin films
[0044] 1. Test the photocurrent-induction time (i~t) curve of the Ir(III) complex 3D film at different times of constant potential polymerization at a bias voltage of -0.4V.
[0045] The photoelectrochemical properties of Ir(III) electropolymerized films were tested using a 500W ultrahigh-pressure spherical xenon lamp high-brightness light source system (Beijing Newbit Technology Co., Ltd.) on a CHI-660E electrochemical workstation with an electrode area of 0.28 cm 2 , the Ir(III) complex 3D film was used as the working electrode, the platinum electrode was used as the counter electrode, the saturated calomel electrode was used as the reference electrode, and the 0.1M Na 2 SO 4 The solution was used as the supporting electrolyte. When the bias voltage was -0.4 V, the photocurrent-induction time (i~t) curves of the Ir(III) complex 3D film were measured for constant potential polymerization for 20s, 40s, 60s, 80s, and 100s. The results are shown in Figure 1 As can be seen from the figure, when the constant potential polymerization time is 60s, the photocurrent of the film is the largest. Therefore, the subsequent experiments take the polymerization time of 60s as an example.
[0046] 2. The bias voltage is -0.4V~+0.4V (the bias voltage change interval is 0.1V), and the photocurrent-induction time (it) curve of the electropolymerized film of the Ir(III) complex with a polymerization time of 60s is tested.
[0047] The it curves of the obtained iridium (III) complex thin film electrode at different bias voltages can be found in Figure 2 As can be seen from the figure, the more negative the applied bias voltage, the stronger the photocurrent of the electropolymerized film. When the applied bias voltage is -0.4V, the photocurrent of the film reaches its maximum value. As the bias voltage becomes more positive, the photocurrent of the film gradually decreases. When the bias voltage is +0.1V, the direction of the photocurrent generated by the film changes. At 100mW / cm 2 Under white light irradiation, the film was electropolymerized at constant potential for 60 seconds in 0.1M Na 2 SO 4 The photocurrent density in aqueous solution is the highest, reaching 7.00 μA / cm 2 It is explained that the polarity of the photocurrent generated by the thin film electrode material is cathode photocurrent, the photocurrent generation efficiency is high, and it can be used as a photoelectric conversion device.
[0048] 3. Test O 2 Effect on the photocurrent density of Ir(III) complex 3D thin films.
[0049] The bias voltage was -0.4 V, and the Ir(III) complex 3D film was measured in air equilibrium and N 2 Balance, O 2 The photocurrent density under equilibrium conditions, the results are shown in Figure 3 At 100mW / cm 2 Under white light irradiation, the film was electropolymerized at a bias voltage of -0.4 V for 60 s at a constant potential in a 0.1 M Na 2 SO 4 The maximum photocurrent density in aqueous solution is 7.00 μA / cm 2 When oxygen was introduced into the electrolyte solution, the photocurrent density increased by 1 times to 14.03 μA / cm 2 , indicating that the film material can be used as an oxygen sensor.
[0050] 4. The photoelectric conversion efficiency IPCE of the Ir(III) complex 3D thin film electrode is calculated using formula (1):
[0051]
[0052] I is the photocurrent density, P inc is the intensity of incident light at a specific wavelength, and λ is the wavelength of the filter.
[0053] When the constant potential electropolymerization was performed for 60 s, the IPCE values of the iridium (III) complex film electrode under monochromatic light of different wavelengths were shown in Figure 2. Figure 4 When the wavelength is 400nm, the photoelectric conversion efficiency is 0.022%, indicating that the film can be used as a photoelectric conversion device.
[0054] The above description is a detailed description of the preferred feasible embodiments of the present invention, but the embodiments are not intended to limit the scope of the patent application of the present invention. All equivalent changes or modified changes completed under the technical spirit suggested by the present invention should fall within the patent scope covered by the present invention.
Claims
1. A carbazole-modified iridium complex, characterized in that: The structural formula of the carbazole-modified iridium complex is shown in formula (I): The chemical formula is [Ir(ppy)2HL]PF6, where ppy represents 2-phenylpyridine and HL is the ligand.
2. The carbazole-modified iridium complex according to claim 1, characterized in that The ligand HL is N-(4-(9H-carbazole-9-yl)phenyl)-4-(9H-carbazole-9-yl)-N-(4-(3a,11b-dihydro-1H-imidazo[4,5-f][1,10]phenanthroline-2-yl)phenyl)aniline, and its structural formula is shown in formula (II):
3. The method for preparing the carbazole-modified iridium complex according to claim 1, characterized in that: The following steps are involved: (1) Synthesis of ligand HL: 4-(bis(4-(9H-carbazole-9-yl)phenyl)amino)benzaldehyde, ammonium acetate, and 1,10-phenanthroline-5,6-dione were placed in a reaction vessel, glacial acetic acid was added, and the reaction was carried out at 120±1° C. After the reaction was completed, the reaction solution was quickly poured into ice water, and the pH of the mixed solution was adjusted to neutral. The solution was allowed to stand for a while, and a precipitate was precipitated and then filtered. The filter cake was washed with distilled water. The crude product was recrystallized with a DMF / H2O mixed solvent, filtered, and the precipitate was collected. The filter cake was washed with anhydrous ethanol and dried in vacuo. The obtained powder was the ligand HL. (2) Synthesis of the complex [Ir(ppy)2HL]PF6: [Ir(ppy)2(μ-Cl)]2 and ligand HL were placed in a flask, and ethylene glycol monoethyl ether was added, and the mixture was refluxed in the dark and under nitrogen protection. After the reaction was completed and cooled to room temperature, NH4PF6 was added to the reaction solution, which was then dried by rotation to obtain a crude product. The crude product was dissolved in dichloromethane and separated and purified by thin layer chromatography on a silica gel column. The orange band was collected and evaporated to remove most of the solvent. Hexane was added until the precipitate was completely precipitated, and the mixture was filtered with suction, and the filter cake was washed with hexane and dried in vacuo to obtain a yellow powder.
4. The preparation method according to claim 3, characterized in that: In step (1), the molar ratio of 4-(bis(4-(9H-carbazole-9-yl)phenyl)amino)benzaldehyde to 1,10-phenanthroline-5,6-dione is 1:
1.
5. The preparation method according to claim 3, characterized in that: In step (2), the molar ratio of [Ir(ppy)2(μ-Cl)]2, ligand HL and NH4PF6 is 1:2:10-20.
6. The preparation method according to claim 3, characterized in that: In step (2), the eluent used for separation and purification is dichloromethane / methanol in a volume ratio of 30:
1.
7. Electropolymerized thin films based on iridium complexes, characterized in that: The electropolymerized film is obtained by modifying the iridium complex described in claim 1 onto an ITO electrode using a constant potential electropolymerization method.
8. The method for preparing an iridium complex-based electropolymerized film according to claim 7, characterized in that: The following steps are involved: First, the ITO glass electrode was cleaned, and then the complex [Ir(ppy)2HL]PF6 was dissolved in a dichloromethane solution containing tetrabutylammonium hexafluorophosphate as a supporting electrolyte. The ITO substrate was used as the working electrode, the platinum electrode was used as the counter electrode, and the Ag / AgNO3 electrode was used as the reference electrode. Under nitrogen protection, constant potential electropolymerization was used to prepare the Ir(III) complex 3D film.
9. The method for preparing an electropolymerized film according to claim 8, characterized in that: The concentration of the iridium complex [Ir(ppy)2HL]PF6 in dichloromethane is 1 mM.
10. The use of the electropolymerized film according to claim 7, characterized in that: Refers to the application of electropolymer films in energy conversion and oxygen sensors.